GRPW-MuS: Geographic Routing to Multiple Sinks in Connected Wireless Sensor Networks - Yassine Sabri (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Multiple sinks routing is envisioned as a possible solution to the bottleneck research problem in Wireless Sensor Networ ks (WSN). In addition to focusing on minimizing the energy consumption in a WSN, it is also equally impor tant to design routing protocols that fair ly and evenly distr ibute the networ k traffic; in order to prolong the networ k life time and improve its scalability.In this paper we present an enhancement to the GRPW algor ithm for wireless sensor networ ks. Perfor mance of GRPW algor ithm algor ithm depends heavily on single sink position , we propose a protocol called GRPW-MuS ( Geographic Routing to Multiple Sinks in connected wireless sensor networ ks) based on Multiple Static Sinks, we modified the existing sink location pr ivacy protection scheme by dividing nodes in the networ k containing multiple sink into different levels in which real packets are forwarded to sink belong to corresponding logical levels and the inter mediate node generating fake packets and sending it to fake sinks. Using OMNET++ simulation and the MiXiM framewor k, it is shown that proposed protocol significantly improves the robustness and adapts to rapid topological changes with multiple mobile sinks, while efficiently reducing the communication overhead and the energy consumption.